Soft tissue reconstruction and visualization for craniofacial surgery planning - Rana, Mohammad Azam (Penerbit UTM, 2007)
Complex maxillofacial malformations continue to present challenges in analysis and correction beyond modern technology. Current surgical procedures attempt to re-establish functional and aesthetic anatomy by repositioning displaced skeletal elements or by grafting and contouring abnormal bony contours. Principally, soft tissue changes are the results of these skeletal alterations.